Analisis Pengaruh Kualitas Konten Promosi Digital, Harga dan Customer Experience Terhadap Purchase Intention Produk Preloved - Aguilika, Deykha; Ibrahim, Mozart Malik; Kholil, Muhammad; Violin, Vivid; Ulimaz, Almira (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the effect of digital promotional content quality, price, and customer experience on purchase intention of preloved products. There is a growing market for pre-owned goods due to the fact that they are both economically beneficial and environmentally friendly. To increase the likelihood that a consumer will make a purchase, digital marketers rely on two factors: the attractiveness of promotional content and the availability of competitive prices and excellent customer service. An online poll was used to collect quantitative data from one hundred people who have shopped for used goods through various marketplaces and social media. Linear regression analyses were performed on the data. The study found that factors such as pricing, customer service, and the quality of digital promotional content significantly impact the inclination to buy used products. In order to enhance their digital marketing tactics, preloved company actors can put these results into practice. By optimizing the visual quality and information of promotional content, setting appropriate prices, and creating a pleasant customer experience, business actors can increase consumer appeal and loyalty to preloved products. This study also opens up opportunities for further research on other factors that can influence purchase intention in the preloved industry.